2007
DOI: 10.1007/s11747-007-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

How consumers’ assessments of the difficulty of manufacturing a product influence quality perceptions

Abstract: This research shows that the perceived difficulty of manufacturing a product influences consumers' perceptions of the firm's other products. In three experiments (with 152 participants in Study 1, 86 in Study 2, and 91 in Study 3), participants received information about the quality of a firm's product and then inferred the quality of another product from the firm. When participants believed that the initial product was relatively more difficult to manufacture than the second product, they inferred that the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…This reaction might be related to the perception of difficulty of manufacture (Johnson and Folkes, 2007), which shares a positive relationship with a consumer's overall evaluation of a brand (Bottomley and Holden, 2001). Therefore, although the technology behind some innovations may not be clearly visible to consumers it appears as if consumers may form a judgment about how technologically innovative a product is and this perception may influence their evaluations of a product's innovativeness.…”
Section: Key Findings and Insights From The Qualitative Researchmentioning
confidence: 99%
“…This reaction might be related to the perception of difficulty of manufacture (Johnson and Folkes, 2007), which shares a positive relationship with a consumer's overall evaluation of a brand (Bottomley and Holden, 2001). Therefore, although the technology behind some innovations may not be clearly visible to consumers it appears as if consumers may form a judgment about how technologically innovative a product is and this perception may influence their evaluations of a product's innovativeness.…”
Section: Key Findings and Insights From The Qualitative Researchmentioning
confidence: 99%
“…Park, Milberg, and Lawson (1991) showed that brand concepts provide a unifying rationale for a brand extension. Additionally, consumers' theorizing about the firm's ability to manufacture a dissimilar product influences generalizations across products in a firm's portfolio (Johnson & Folkes, 2007). As to brand alliances, theorizing about the rationale for a partnership seems to occur for independent brands that partner with each other on a new product (Walchli, 2007).…”
Section: Managerial Control As a Basis For Consumers' Inferencesmentioning
confidence: 99%
“…First, consumer expectations about the difficulty of producing the extension may influence their comprehension of the benefits of the extension product and their subsequent adoption (Wood and Moreau 2006). Second, extension difficulty is likely to act as a source of diagnostic information when making inferences about the new brand extension (e.g., DelVecchio and Smith 2005;Johnson and Folkes 2007). When high-quality brands extend into trivial product categories, like Haagen Dazs popcorn, consumers are thought to use perceived difficulty as a cue about the motivations (e.g., "exploitative") of the proposed brand extension (see Aaker and Keller 1990).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…From a theoretical perspective, the role of extension difficulty as a key determinant of brand extension attitudes has been amply explicated in the marketing literature (Aaker and Keller 1990;Johnson and Folkes 2007). Aaker and Keller (1990) posited a positive effect of extension difficulty on brand extension attitudes by laying out a well-reasoned explanation.…”
Section: Introductionmentioning
confidence: 99%